Challenges for the implementation of gender equality policies in the context of public companies in Argentina (2020-2021) - González, Victoria; Yañez, Manuel (Journal Studies of Public Policy, 2022)
The objective of this article is to analyze the implementation process of gender and diversity policies in public companies in Argentina between 2020 and 2021. This work an exploratory study with a mixed research strategy. On the one hand, theoretical and empirical contributions, as well as regulations that impact the implementation of gender and diversity policies in public companies were collected, while on the other hand, in-depth interviews were conducted with people responsible for implementing these policies within the companies. In concrete terms, this work shows the main findings of the first stage of interviews, organized around three areas: key gender issues identified in the companies, level of institutionalization of existing gender spaces, and developed strategies, and obstacles and challenges to implement gender actions. Lastly, it analyzes how the hybrid nature of these organizations and their relationship with ministerial authorities can favor and contribute to the uniqueness of the implementation of gender actions.